ANALISIS KIMIA KAYU KARET ( Heavea brasiliensis Muell. Arg. ) DIAWETKAN SECARA TRADISIONAL - Agus Ismanto; Yudi Dwi Saputro (JURNAL SAINS NATURAL, 2014)
Chemical Analysis of Wood Rubber (Heavea brasiliensis Muell. Arg.) Preserves in Traditional         Rubber wood (Hevea brasiliensis Muell.Arg.) is one type of wood is not preserved, so it is easily attacked by wood destroying insects such as dry powder beetles, dry wood termites, termites, and ambrosia beetles. To solve this problem was the preservation of wood, both in traditional or modern. The preservation of wood in the traditional way, such as by immersion in water, boiling and steaming. In this research, analysis of levels of starch, cellulose and lignin in rubber wood, marinated, boiled or steamed. The goal was to determine the levels of starch, cellulose and lignin in rubber wood that has been given the treatments compared to the control. Soaking process conducted for 3, 7 and 14 days. While boiling and steaming during 0.5, 1 and 2 hours. The analyzes were performed with Luff-Schoot method for the determination of levels of starch and Chesson method for determination of cellulose and lignin. Strach and lignin analysis results indicated a declining trend in treatment for soaking, boiling and steaming compared with controls. But not so in the levels of cellulose. The conclusion was soaking in water for 7 days or boiling or steaming for 1 hour already could lower levels of starch.Keywords: rubber wood, traditional preservation, starch, cellulose, lignin. ABSTRAK        Kayu karet ( Hevea brasiliensis Muell.Arg. ) merupakan salah satu jenis kayu yang tidak awet, sehingga mudah diserang oleh serangga perusak kayu seperti kumbang bubuk kering , rayap kayu kering, rayap tanah, dan kumbang ambrosia. Untuk mengatasi masalah tersebut perlu dilakukan pengawetan kayu baik secara tradisional maupun modern. Pengawetan kayu dengan cara tradisional, antara lain dengan cara perendaman dalam air , perebusan dan pengukusan. Pada penelitian ini dilakukan analisa kadar pati, selulosa dan lignin  pada kayu karet yang direndam , direbus atau dikukus. Tujuannya adalah untuk mengetahui kadar pati, selulosa dan lignin pada kayu karet yang sudah diberi perlakuan tersebut dan dibandingkan dengan kontrol. Proses perendaman yang dilakukan selama 3, 7 dan 14 hari. Sedangkan perebusan dan pengukusan selama 0,5 , 1 dan 2 jam. Analisa dilakukan dengan metode Luff-Schoot untuk penetapan kadar pati dan metode Chesson untuk penetapan  kadar selulosa dan lignin. Hasil analisa kadarpati dan lignin menunjukkan adanya kecenderungan penurunan pada perlakuan perendaman , perebusan dan pengukusan dibandingkan dengan kontrol. Tetapi tidak demikian pada kadar selulosanya. Kesimpulannya adalah perendaman dalam air selama 7 hari atau perebusan atau pengukusan selama 1 jam sudah dapat menurunkan kadar pati.Kata kunci : kayu karet, pengawetan tradisional, pati, selulosa, lignin.